Ground-based tests of JEM-EUSO components at the Telescope Array site, "EUSO-TA" - Adams, J. H. (2015)
We are conducting tests of optical and electronics components of JEM-EUSO at the Telescope Array site in Utah with a ground-based "EUSO-TA" detector. The tests will include an engineering validation of the detector, cross-calibration of EUSO-TA with the TA fluorescence detector and observations of air shower events. Also, the proximity of the TA?s Electron Light Source will allow for convenient use of this calibration device. In this paper, we report initial results obtained with the EUSO-TA telescope.